2020
DOI: 10.1128/jcm.01649-19
|View full text |Cite
|
Sign up to set email alerts
|

Building a Better Test for Piperacillin-Tazobactam Susceptibility Testing: Would that It Were So Simple (It's Complicated)

Abstract: In this issue of the Journal of Clinical Microbiology, S. García-Fernandez, Y. Bala, T. Armstrong, M. Garcia-Castillo, et al. (J Clin Microbiol 58:e01042-19, 2020, https://doi.org/10.1128/JCM.01042-19) describe the performance of a reformulated Etest for piperacillin-tazobactam. The analytical performance data are excellent, but in the face of recent emerging data on the inefficacy of piperacillin-tazobactam for certain organisms that test susceptible, the value of piperacillin-tazobactam MICs is controversial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…This is especially important to note, as Etest strips had previously been noted to be unreliable for testing piperacillin/tazobactam. 217 …”
Section: Current Therapiesmentioning
confidence: 99%
“…This is especially important to note, as Etest strips had previously been noted to be unreliable for testing piperacillin/tazobactam. 217 …”
Section: Current Therapiesmentioning
confidence: 99%
“…Piperacillin-tazobactam AST in particular was most problematic and gave the highest number of VMEs, most of which occurred with E. coli but also with Klebsiella spp. This is not completely surprising following emerging evidence of performance and consistency issues with piperacillin-tazobactam AST ( 15 ). Previous studies using clinical isolates or samples with the dRAST have shown a low overall VME, ME, and mE rate; however, it seems that the total number of isolates were considered for error rate calculation ( 7 , 10 , 11 ).…”
Section: Discussionmentioning
confidence: 97%
“…At a later stage, commercial devices may be identified as having significant problems leading to very major errorsda situation where isolates resistant to a trial antimicrobial are incorrectly categorized as susceptible by the local AST device or method [24e27]. In cases where issues with commercial AST devices are identified by standards-setting bodies such as EUCAST, laboratories that continue to use these devices are at increased risk of reporting false susceptibility to one or both of the trial antimicrobials [28,29]. A clear example of this is for colistin, where many laboratories across multiple trials (AIDA, CARE, MAGIC BULLET) used commercial methods with known problems rather than recommended broth microdilution resulting in significant AST error rates for colistin [30e34].…”
Section: Discussionmentioning
confidence: 99%
“…MIC are variable regardless of method used. Reading broth microdilution plates requires training and skill and when target isolates have MICs that challenge the clinical breakpoint of the antimicrobials, high categorical error rates are not unexpected, even if essential agreement is close to 100% (defined as within 1 dilution of the reference method MIC) [28]. Reflecting this issue, six out of ten isolates from excluded patients from RESTORE IMI had a difference of one dilution for colistin and imipenem/relebactam between reference and commercial method [36].…”
Section: Discussionmentioning
confidence: 99%